Structural behavior of concrete girders prestressed and reinforced with stainless steel materials. (January 2022) - Al-Kaimakchi, Anwer; Rambo-Roddenberry, Michelle
Abstract: Stainless steel reinforcing rebars and prestressing strands are viable alternatives to carbon steel materials for prestressed concrete structures in extremely aggressive environments. They offer better durability and require less maintenance. This study experimentally investigated the transfer length and prestress losses of 15.2-mm- (0.6-in.-) diameter Duplex High-Strength Stainless Steel (HSSS) strands as well as the shear and flexural behavior of two full-scale 12.8-m- (42-ft-) long AASHTO Type II concrete girders prestressed with HSSS strands and reinforced with duplex stainless steel rebars. The girders were made composite by adding a deck slab. One girder was tested in shear at both ends while the other girder was tested in flexure. Experimental shear and flexural behavior of the girders exhibited a constant increase in load carrying capacity up to failure. The failure mode for the shear tests was web shear, and for the flexural test was rupture of the HSSS strands. Both girders tested in shear and flexure failed in a progressive manner as they exhibited adequate warning through noticeable deflection, excessive cracking, and large reserve strength from first cracking to failure. The applicability of AASHTO LRFD provision for stainless steel reinforcing materials was investigated. AASHTO LRFD equations for flexural resistance were modified to cover rupture of strand failure mode. Experimental shear strength and flexural strength of the girders were greater than the predicted values by AASHTO shear equations and modified AASHTO flexural equations, respectively.